0179 Independent Medical Evaluations - Important, neglected, in need of reform: a systematic review. (23rd June 2014) - Busse, Jason; Ebrahim, Shanil; Riva, John; Bance, Sheena; Guyatt, Gordon; Bagby, Michael; Kunz, Regina
Abstract : Objectives: Independent medical evaluations (IMEs) are a common and influential form of assessment, often influencing whether patients receive compensation for an injury or illness. To inform the evidence-base underlying IMEs, we conducted a systematic review of all primary literature conducted in North America. Method: We searched CINAHL, EMBASE, MEDLINE and PsycINFO and other sources for studies published through to Sept. 20, 2011. We included all primary literature on the topic of IMEs from a North American perspective. Assessment for study inclusion, data extraction and risk-of-bias analyses were performed in duplicate. Results: We included 52 studies, all of which were observational in design and most of which focussed on determining the rate of malingering among examinees. Estimates of non-credible symptom over-reporting among patients presenting for IMEs ranged from 16% to 55%, with studies at lower risk of bias finding higher estimates. Other studies found that inter-rater reliability among IME assessors for assigning degree of impairment to the same IME report was poor, and that patients presenting for an IME with external incentive (e.g. litigation, disability benefits) perform systematically worse across a range of psychometric tests versus patients presenting with similar illness/injury but without external incentive. Conclusions: Symptom exaggeration is common among patients presenting for IMEs, and particularly among those patients with external incentive. IME assessors reviewing the same case demonstrate little agreement regarding the degree of impairment that should be assigned. Standards for IME assessment and reporting are urgently needed to ensure greater reliability and validity of this common form of assessment.